Ultrafast Charge Transfer in Operating Bulk Heterojunction Solar Cells. (13th February 2015) - Zhong, Chengmei; Choi, Hyosung; Kim, Jin Young; Woo, Han Young; Nguyen, Thanh Luan; Huang, Fei; Cao, Yong; Heeger, Alan J.
Abstract : The ultrafast charge generation process in organic solar cell devices is investigated by transient reflection spectroscopy on five state‐of‐the‐art bulk heterojunction systems. The charge generation process in operating devices is found to be a combination of an ultrafast generation mechanism over several hundred femtoseconds and a slow process from picoseconds to nanoseconds, limited by exciton diffusion dynamics. In addition, the lack of electric field dependence in the charge dynamics rules out geminate recombination as an important loss mechanism.